Submergence tolerant rice - Ismail, Abdelbagi M. (International Rice Research Institute, 2014)
Presentation by Rona Azucena on behalf of Dr. Abdelbagi M. Ismail (International Rice Research Institute) at the Global Forum for Innovations in Agriculture (GFIA), February 4, 2014